Development of a Basilar Membrane-Inspired Mechanical Spectrum Analyzer Using Metastructures for Enhanced Frequency Selectivity - Shantanu H. Chavan; Vijaya V. N. Sriram Malladi (Actuators)
This study introduces a mechanical spectrum analyzer (MSA) inspired by the tonotopic organization of the basilar membrane (BM), designed to achieve two critical features. First, it replicates the traveling-wave behavior of the BM, characterized by energy dissipation without reflections at the boundaries. Second, it enables the physical encoding of the wave energy into distinct spectral components. Moving beyond the conventional focus on metamaterial design, this research investigates wave propagation behavior and energy dissipation within metastructures, with particular attention to how individual unit cells absorb energy. To achieve these objectives, a metastructural design methodology is employed. Experimental characterization of metastructure samples with varying numbers of unit cells is performed, with reflection and absorption coefficients used to quantify energy absorption and assess bandgap quality. Simulations of a basilar membrane-inspired structure incorporating multiple sets of dynamic vibration resonators (DVRs) demonstrate frequency selectivity akin to the natural BM. The design features four types of DVRs, resulting in stepped bandgaps and enabling the MSA to function as a frequency filter. The findings reveal that the proposed MSA effectively achieves frequency-selective wave propagation and broad bandgap performance. The quantitative analysis of energy dissipation, complemented by qualitative demonstrations of wave behavior, highlights the potential of this metastructural approach to enhance frequency selectivity and improve sound processing. These results lay the groundwork for future exploration of 2D metastructures and applications such as energy harvesting and advanced wave filtering.